1997
DOI: 10.1161/01.cir.95.1.176
|View full text |Cite
|
Sign up to set email alerts
|

ACE Inhibitors Promote Nitric Oxide Accumulation to Modulate Myocardial Oxygen Consumption

Abstract: Our data indicate that stimulation of local kinin formation by use of a precursor for kinin formation or inhibition of kinin degradation by use of ACE inhibitors increases NO formation and is important in the control of cardiac O2 consumption. Vasodilation and control of myocardial O2 consumption by NO may contribute importantly to the therapeutic actions of ACE inhibitors in cardiac disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(93 citation statements)
references
References 37 publications
8
81
1
3
Order By: Relevance
“…Studies by Hintze et al have shown that endothelium-derived NO reduces myocardial O 2 consumption and influences substrate utilization, the net effect being an increase in cardiac efficiency. 2,14,32 These investigators recently also reported that in canine pacinginduced heart failure, development of decompensated heart failure was accompanied by a reduction in total cardiac NO x production, a switch in myocardial substrate utilization from free fatty acids to glucose, a decrease in cardiac efficiency, and diastolic dysfunction. 32 Whether the same applies in pressure-overload LVH merits investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Studies by Hintze et al have shown that endothelium-derived NO reduces myocardial O 2 consumption and influences substrate utilization, the net effect being an increase in cardiac efficiency. 2,14,32 These investigators recently also reported that in canine pacinginduced heart failure, development of decompensated heart failure was accompanied by a reduction in total cardiac NO x production, a switch in myocardial substrate utilization from free fatty acids to glucose, a decrease in cardiac efficiency, and diastolic dysfunction. 32 Whether the same applies in pressure-overload LVH merits investigation.…”
Section: Discussionmentioning
confidence: 96%
“…*PϽ0.05, **PϽ0.01. ACE inhibition has previously been shown to promote NO accumulation in coronary microvessels, 31 and certain salutary effects of ACE inhibitors on vasomotor reactivity have been linked to augmented NO release. [32][33][34] Moreover, NO may completely abrogate the caspace cascade activated by Ang II and shown by Dimmeler et al 35 to induce apoptosis of human umbilical vein ECs.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by studies in myocardial tissue demonstrating that oxidative metabolism and myocardial performance is dependent on a balanced ACE activity. 75,198 Further investigations in this area are clearly required to more thoroughly evaluate this concept. …”
Section: Perspectivesmentioning
confidence: 99%